Bound Peptide-Dependent Thermal Stability of Major Histocompatibility Complex Class II Molecule I-Ek - Saito, Keigo; Oda, Masayuki; Sarai, Akinori; Azuma, Takachika; Kozono, Haruo (Biochemistry (Easton), 2004)
We used differential scanning calorimetry to study the thermal denaturation of murine major histocompatibility complex class II, I-Ek, accommodating hemoglobin (Hb) peptide mutants possessing a single amino acid substitution of the chemically conserved amino acids buried in the I-Ek pocket (positions 71 and 73) and exposed to the solvent (position 72). All of the I-Ek-Hb(mut) molecules exhibited greater thermal stability at pH 5.5 than at pH 7.4, as for the I-Ek-Hb(wt) molecule, which can explain the peptide exchange function of MHC II. The thermal stability was strongly dependent on the bound peptide sequences; the I-Ek-Hb(mut) molecules were less stable than the I-Ek-Hb(wt) molecules, in good correlation with the relative affinity of each peptide for I-Ek. This supports the notion that the bound peptide is part of the completely folded MHC II molecule. The thermodynamic parameters for I-Ek-Hb(mut) folding can explain the thermodynamic origin of the stability difference, in correlation with the crystal structural analysis, and the limited contributions of the residues to the overall conformation of the I-Ek−peptide complex. We found a linear relationship between the denaturation temperature and the calorimetric enthalpy change. Thus, although the MHC II−peptide complex could have a diverse thermal stability spectrum, depending on the amino acid sequences of the bound peptides, the conformational perturbations are limited. The variations in the MHC II−peptide complex stability would function in antigen recognition by the T cell receptor by affecting the stability of the MHC II−peptide−T cell receptor ternary complex.